2006
DOI: 10.1021/jp055268x
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Adsorption of NO, NO2, CO2, and H2O on BaO(100):  A Quantum Chemical Study

Abstract: Density functional theory (DFT) quantum chemical calculations are used to determine adsorption energies and geometries of NO, NO(2), CO(2), and H(2)O on a barium oxide (100) surface. The study includes two adsorption geometries for NO(2). All species form thermodynamically stable adsorbates, and adsorption strength increases in the order NO(2) < H(2)O < NO Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 46 publications
4
57
2
1
Order By: Relevance
“…Along these lines, it was argued that bulk Ba(NO 3 ) 2 could not be formed through the interaction of NO x (g) with bulk BaCO 3 under operational conditions. On the other hand, denisty functional theory (DFT) calculations associated with NO 2 and CO 2 adsorption on the BaO(100) 9 and BaCO 3 (110) 10 surfaces revealed that, although the adsorption strength of CO 2 is higher than that of NO 2 on BaO(100), 9 NO 2 adsorption on the BaCO 3 (110) surface should not be excluded. 10 On the BaO(100) surface, CO 2 was reported to adsorb exclusively on the Lewis base (i.e., O 2− ) sites forming surface carbonates, 9 while on the stoichiometric BaCO 3 (110) surface, CO 2 was reported to adsorb also on the Lewis acid sites (i.e., Ba 2+ ).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Along these lines, it was argued that bulk Ba(NO 3 ) 2 could not be formed through the interaction of NO x (g) with bulk BaCO 3 under operational conditions. On the other hand, denisty functional theory (DFT) calculations associated with NO 2 and CO 2 adsorption on the BaO(100) 9 and BaCO 3 (110) 10 surfaces revealed that, although the adsorption strength of CO 2 is higher than that of NO 2 on BaO(100), 9 NO 2 adsorption on the BaCO 3 (110) surface should not be excluded. 10 On the BaO(100) surface, CO 2 was reported to adsorb exclusively on the Lewis base (i.e., O 2− ) sites forming surface carbonates, 9 while on the stoichiometric BaCO 3 (110) surface, CO 2 was reported to adsorb also on the Lewis acid sites (i.e., Ba 2+ ).…”
Section: ■ Introductionmentioning
confidence: 99%
“…This agreement may be a coincidence, or it may indicate that CO 2 can have a similar adsorption mechanism on stoichiometric TiO 2 and BaTiO 3 surfaces at room temperature. ͓CO 2 can adsorb on stoichiometric oxide surfaces at cation or anion sites in a variety of bonding configurations, but theoretical studies have indicated that while CO 2 adsorbs preferentially at cation sites on various TiO 2 surfaces, 45,46 it prefers oxygen anion sites on BaO͑100͒, 47 BaTiO 3 ͑001͒, 48 and both SrO-and TiO 2 -terminated SrTiO 3 ͑001͒ surfaces. 49 ͔ In addition, a dramatic increase in the chemisorption energy of CO 2 on SrTiO 3 ͑100͒ is observed at oxygen vacancy sites induced by Ar-ion sputtering, resulting in a TPD peak at 650 K. 42 This is consistent with the assignment of peak D in Fig.…”
Section: L15mentioning
confidence: 99%
“…Thus, we performed a density functional theory (DFT) study of CO 2 adsorption on the BaO surface in the presence of H 2 O to understand the chemical activity of the oxygen site on BaO adsorbents and to establish the molecular structures and molecular reaction mechanisms of mineral carbonation because a DFT calculation yields high accuracy for adsorption energy and geometry with low cost. 11,14 First, this study performs the adsorption energies and geometries of single CO 2 molecule and single H 2 O molecule on the BaO (100) surface in the periodic-slab model. To determine the role of H 2 O molecule, we represent the adsorption characteristics of a pair of H 2 O molecules on the BaO (100) surface, and then that of one CO 2 molecule and one H 2 O molecule, which are bound to distant and neighboring sites on the surface.…”
Section: Introductionmentioning
confidence: 99%